Optimization of Reactive Ion Etching (RIE) Process Using SF6 and CHF3 Gases - Mohd Noor, Muhammad Hidayat; Nayan, Nafarizal (Evolution in Electrical and Electronic Engineering, 2022)
Reactive ion etching (RIE) is a technology of etching that is used in microfabrication and one of the methods of dry etching and has different characteristics compared to wet etching. The chemical process of the reactive plasma from the RIE is used to remove materials deposited on the wafer. The RIE etcher has several variable factors such as RF power, pressure, gas flow rate, and etching time that correspond to output parameters of its etching depth and its etching rate. There are many numbers of experiments needed to be run to find the optimum setting of RIE to establish the ideal conditions for the output etching rate. In this study, Si and SiO2 wafers are used to etch using the process gas of SF6 and CHF3 that feed to the RIE system. The etching depth and etching rate were investigated by using Dektak XT Bruker Surface Profiler and also to characterize the surface roughness of etched Si and SiO2 by using 3D mapping mode. The result shows the effect between varied RF power, time and flow rate on the etching depth and rate so the optimum parameters can be selected.